HOUSEHOLD GARDENING AS PREFERENCE ACTIVITIES TO SUPPORT COMMUNITY RESILIENCE DURING PANDEMIC COVID-19 - Irina Mildawani; Arief Rahman (Journal of Synergy Landscape, 2021)
The COVID-19 pandemic in 2020 affected countries across the world and sudden disruptions to everyday life and impact well-being. The implementation of exceptional procedures of social distancing includes working places and schools’ closures urged people to stay at home to reduce the number of close physical interactions and decrease the spreading of pandemic. With the long hours of family members staying at home, people prefer to do some activities at home. Doing gardening is seen as one of the preferences of urban inhabitants. However, few studies have measured the preference of urban gardening, particularly during household gardening in Jabodetabek, Indonesia. This paper examines people preferences on household gardening during the pandemic of Covid-19, comparing it with their activities before and predict it with possibility after the pandemic. We explore how type of gardening varies between vegetable or ornamental plants, community or household garden type, and the persons involved during gardening. Using google form, 148 respondents in Jabodetabek were answering between July-Dec 2020. Our study examines the emotional well-being (EWB) using Qualitative Content Analysis (QCA), applying codes and categories. Gardening as one of the favorable activities considered to generate happy time with family and they would like to continue the activities after the pandemic. However, landscape architect was not yet chosen as the gardener when they need professional assistance.  This might rise a future research about the role of landscape architect in gardening movement in urban community gardening